Increased biomass and carbon burial 2 billion years ago triggered mountain building - John Parnell (Nature Portfolio, 2021)
High burial of organic carbon in sediments around 2 billion years ago acted to enhance crustal deformation and led to intensified mountain building both in the Paleoproterozoic and since, suggests an assessment of the timing of carbon burial and deformation